Reduced-Size Series-Fed Two-Dipole Endfire Antenna - 왕희수; 박용배; 박익모 (Journal of Electromagnetic Engineering and Science, 2022)
The conventional series-fed endfire dipole antenna has a wide impedance bandwidth and is inexpensive to manufacture. However, it has a disadvantage: its size is large because of the large inter-dipole spacing, which is required to satisfy the endfire condition for good antenna radiation characteristics. Here, we propose a two-dipole endfire antenna with a reduced size. The miniaturized endfire antenna was designed using a meander line to reduce the interdipole spacing while ensuring that the endfire condition was satisfied. Furthermore, the overall width of the antenna was reduced using a bent dipole and a corrugated ground plane. The electrical size of the proposed antenna was only 0.33λo × 0.33λo × 0.014λo at a center frequency of 5 GHz, its −10 dB impedance bandwidth was 4.47–5.72 GHz (24.5%), and the gain at the center frequency was 5.9 dBi.
Keywords: C-Band Antenna; Dipole Antenna; Endfire Antenna; Miniaturized Antenna; Printed Dipole Antenna.